Theory and practice of building community resilience to extreme events. (1st June 2021) - Robertson, Tony; Docherty, Paul; Millar, Fiona; Ruck, Andy; Engstrom, Sandra
Abstract: Community resilience represents the ability of communities to use their available resources to prepare for, respond to, endure, and recover from extreme events such as floods, economic shocks and disease outbreaks. Despite a wide range of definitions and studies into community resilience, there is a lack of clarity about what community, practice and policy stakeholders understand it to represent, and how communities can practically develop such resilience. In this article, we present findings from two workshops with a range of stakeholders across communities, policy, academia and the statutory sector to gain an understanding of the current state of knowledge about community resilience to extreme events in the UK, including examples of current practice and how to collaborate better. From our workshops seven key themes about what makes communities resilient were identified: social ties and connections; experience and shared memory; leadership, engagement and shared responsibility; mind-set, collective thinking, openness to adapt and cultural change; integration, inclusivity, equity and diversity; communications, social support and co-ordination; and training and exercises and identifying local needs. How we develop resilient communities is by no means straightforward; resilience is not an outcome, rather a process (or perhaps a state of becoming?). However, this study has combined the evidence base on community resilience with qualitative inputs from a range of community, policy and academic stakeholders to provide a novel perspective on what community resilience is and how it can be developed.